STUDI PERENCANAAN JEMBATAN BETON PRATEKAN - Bowo Leksono (Wahana Teknik, 2012)
With a growing population, traffic density will grow well from one region to another. Therefore, the number of passenger car units that pass through the highway will continue to increase as well, so that the daily traffic volume reached over 20 000 smp. Therefore, the construction of the bridge with high capacity is required. Thus the construction of reinforced concrete bridges and construction of prestressed concrete (prestressed concrete) is indispensable presence. Construction of reinforced concrete and prestressed concrete kosntruksi initially quite expensive compared to using other construction materials, but given the relatively low maintenance cost for long term economic value is very profitable.Broadly speaking, the bridge consists of building up and building down. Superstructure consists of pavement, the vehicle floor, which is the main beam kosntruksi prestressed concrete. While the building is a pillar of the bridge, the bridge head, beams and piles Poer.In the analysis refers to the regulation of construction charge for Highway Bridges 1970 (PMJJR "70) and Indonesia Reinforced Concrete Regulation 1971 NI-2 (PBI '71). There are two kinds of concrete construction is of reinforced concrete construction (reinforced concrete) method of boundary strength (ultimate strength analysis) and construction of prestressed concrete (prestressed concrete) method comparable strength (load balancing method) with a parabolic tendon. Using the foundation piles.For large concrete bridge spans a very profitable given the treatment does not require great expense to the construction of prestressed concrete primarily to address the effect of the earthquake with the concept of partial prestressing.Keywords : Concrete Construction, power limits, prestressed force balance (load balancing method)